Pelatihan Ecoprint dengan Metode Pounding pada Produk Bernilai Jual sebagai Bentuk Kesadaran Lingkungan Bagi Kelompok Wanita Tani (KWT) di Desa Karakan Kecamatan Weru Kabupaten Sukoharjo - Prayudias Margawati; Aisyaah Muthiati; Nova Laurina Ramadhani (Universitas Negeri Semarang, 2026)
The natural potential of Karakan Village, Weru District, Sukoharjo Regency is diverse, but it still lacks consideration for environmental sustainability, resulting in low community awareness of environmental issues. Additionally, the underutilization of natural resources has left the community unable to fully harness the available natural potential. To address these challenges, students college from GIAT 9 UNNES conducted an ecoprint training using the pounding method for the Women Farmers Group (KWT) in Karakan Village. This training aimed to raise environmental awareness and provide new skills that could enhance the community's economic value. Through the pounding method, training participants were taught to create ecoprint products that are highly aesthetic and environmentally friendly. The training results showed an improvement in the participants' skills and understanding, which is expected to contribute to environmental preservation and increase the economic welfare of the Karakan Village community. This training is also in line with the community empowerment efforts initiated by the local government and is expected to serve as a model for other villages in developing sustainable handicraft industries.